Dramaturgi Dalam Media Sosial: Second Account Di Instagram Sebagai Self Disclosure - Bilqis, Tri Dewi; Alfiani, Muhammad Raudan; Gayatri, Futry Ayu; Cuhandi (HUMANUS : Jurnal Sosiohumaniora Nusantara, 2024)
This study explores the phenomenon of using second accounts on Instagram as a form of self-disclosure with a dramaturgical approach in the context of social media, particularly among students of the Faculty of Communication Sciences at Djuanda University. Adopting Erving Goffman's dramaturgical theory, the research identifies the second account as part of the backstage, where individuals can design roles and self-presentations without the constraints of their main accounts. Within the framework of self-disclosure theory, students are highlighted for voluntarily disclosing personal information on social media to build interpersonal relationships. The research employs a qualitative descriptive method, involving observations and in-depth interviews with students. The results indicate that students with second accounts act as digital dramaturges, preserving privacy, enhancing creativity, and reinforcing their online identities through self-disclosure. This study provides a profound understanding of dramaturgy in social media, particularly the use of second accounts on Instagram as a form of self-disclosure, demonstrating that digital dramaturgy has become a complex and relevant strategy in the era of social media.